Synthesis and Characterization of Silver Nanoparticle-Polydimethylsiloxane (Ag-NP-PDMS) Stretchable Conductive Nanocomposites - Abdul Rauf Jamali; Jahanzeb Bhatti; Waseem Khan; Faheem Akther; Madiha Batool; Razia Batool; Walid M. Daoush (Crystals, 2022)
A number of different research methodologies have been developed to increase the conductivity and mechanical properties of stretchable or flexible conductors. One of the promising techniques recommended for applying metallic nanoparticles (NPs) to PDMS (polydimethylsiloxane) substrate is to develop a thin-film that gives possible conductivity and good mechanical strain. This article discusses the preparation of silver nanoparticles using the chemical reduction method with silver nitrate as the precursor, and uses glucose as a reducing agent. In addition, polyvinyl pyrrolidone (PVP) is used to prevent the nanoparticles’ oxidation and agglomeration once they have been synthesized successfully. Moreover, we utilize the power of diethylamine to accelerate the evolution of nanoparticles, and deionized water is used to prevent any possible contamination. The prepared Ag-NPs are then deposited on the solidified PDMS substrate through sintering. A multimeter is used to measure the electrical resistance. Ag-NPs are confirmed by UV-Vis at a 400-nm peak. Furthermore, we discuss the surface morphologies, particle sizes and thicknesses of the film and substrate when studied using different microscopy techniques. The prepared stretchable conductor is found to be suitable to use in biosensing and electronic devices.